The Negative Impact of Parking Lots on Walkability - Isla Leadbetter; Angel Emmanuel Hernandez Cruz; Léa Ravensbergen; Anastasia Soukhov (Findings)
Parking lots are surprisingly understudied in walkability research. Using an audit, this article examines how parking lots impact walkability at care destinations in Hamilton, Ontario. Parking lots are found to negatively - and substantially - impact walkability; their objective walkability score is half that of other road segments and 3.5 times lower than pedestrian and bicycle streets. Correlation analysis suggests low scores are related to parking lot’s frequent absence of walkable features, such as pedestrian facilities and traffic control elements. Removing parking lots would increase urban walkability. When this is not feasible, incorporating design elements can improve parking lot walkability.